2008
DOI: 10.1111/j.1600-0560.2007.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological study of involucrin expression in Darier's disease skin

Abstract: DD skin displayed a constant immunohistochemical involucrin pattern characterized by both premature expression and a particular cytoplasmic/cell membrane localization distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
3
8
0
1
Order By: Relevance
“…1d); this is consistent with a previous report by Aberg et al. 18 In line with these data, immunohistological studies of involucrin expression in skin samples from patients with HHD revealed reduced involucrin expression 19 . Taken together, our data and that of other groups indicate that HHD keratinocytes derived from lesional skin retain their cell‐specific characteristics in culture.…”
Section: Resultssupporting
confidence: 93%
“…1d); this is consistent with a previous report by Aberg et al. 18 In line with these data, immunohistological studies of involucrin expression in skin samples from patients with HHD revealed reduced involucrin expression 19 . Taken together, our data and that of other groups indicate that HHD keratinocytes derived from lesional skin retain their cell‐specific characteristics in culture.…”
Section: Resultssupporting
confidence: 93%
“…In addition to changes in keratin expression, the expression of other proteins, such as involucrin, also characterizes terminal differentiated keratinocytes in lining epithelia [50]. Thus, the development of keratinocyte phenotype was assayed by gene expression of involucrin and keratins 1, 10 and 14.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes and epidermis form a unique model to study ER stress, particularly ER stress due to ER Ca 2+ depletion. Profound ER Ca 2+ depletion, caused by a variety of mutations in the ER Ca 2+ ATPase ATP2A2 (protein SERCA2), leads to Darier disease, a skin condition characterized by defective keratinocyte differentiation, abnormal keratinocyte apoptosis and impaired cell‐to‐cell adhesion known as acantholysis 4–6 . When SERCA2 is inactivated in mice, altered differentiation leads to development of squamous cell carcinomas in these animals’ skin 7 .…”
mentioning
confidence: 99%